Kadar Hemoglobin pada Pasien Diabetes Mellitus Tipe 2 - Wahyu Anita Khoirin; Rodhi Hartono (Jaringan Laboratorium Medis, 2021)
Type 2 diabetes mellitus with chronic hyperglycemia can cause a hypoxic environment in the renal interstitium and can cause kidney disorders (diabetic nephropathy), this can lead to decreased kidney function and the production of erythropoietin produced by peritubular fibroblasts is disrupted, and hemoglobin is not formed optimally and occurs anemia. Thei purposei ofi thisi studyi wasi toi determinei hemoglobini levelsi in patients withi typei 2i diabetesi mellitusi in RSUD. K.R.M.T Wongsonegoro Semarang. This is a descriptive quantitative study, the data comes from the medical records of patients with typei 2i diabetesi mellitusi withi complicationsi ofi diabetici nephropathyi at RSUD K.R.M.T Wongsonegoro Semarang as many as 40 samples with non-probability samplingi itechnique. The results showed that there were 20 men who had decreased hemoglobin levels and 1 person who had normal hemoglobin levels. Meanwhile, in women, 17 people had decreased hemoglobin levels and 2 people had normal hemoglobin levels. Based on the age category, the most were the early elderly as many as 15 people and the least in the late teens and early adults each as many as 2 people. Meanwhile, based on the average level of anemia, more experienced moderate levels of anemia. Hemoglobin levels in patients with type. 2i. diabetesi. mellitusi. withi. complicationsi. ofi. diabetici. nephropathyi. at RSUD K.R.M.T Wongsonegoro Semarang were 40 samples, on average they had low hemoglobin levels.